Pengaruh Job Insecurity dan Emotional Exhaustion terhadap Kinerja Perawat RSU Tangerang - Guruh, Muhamad; Suryani, N Lilis; Syatoto, Iman; Darmadi, Darmadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The increasing demand for high-quality healthcare services has made the performance of nurses a critical component in achieving organizational effectiveness, particularly in public hospitals. However, contract nurses often face psychological pressures that can affect their work performance. This study was conducted to investigate the influence of job insecurity and emotional exhaustion on the performance of contract nurses at RSU Tangerang, addressing a pressing issue in human resource management in the healthcare sector. Using a quantitative approach with an associative research design, data were collected from 150 contract nurses, selected from a population of 240 using the Slovin formula. The data were obtained through closed-ended questionnaires distributed via WhatsApp, using a Likert scale for measurement. Analysis was conducted using multiple linear regression with SPSS 25. The findings reveal that both job insecurity and emotional exhaustion negatively affect nurse performance. Job insecurity leads to reduced motivation and a sense of uncertainty, while emotional exhaustion diminishes energy and professional engagement. These results imply that improving employment stability and providing emotional support are essential strategies for hospital management to enhance nurse performance. Future policy and managerial decisions should consider these psychological aspects to maintain service quality and workforce sustainability.